Community Understanding of the Importance of Education in Rumberu Village, Inamosol District, West Seram Regency - Soemarsono, Klinton; Tuharea, Jumiati; Soumokil, Agustinus (CV. Rayyan Dwi Bharata, 2023)
This research is a qualitative descriptive study which aims to find out how the community understands the importan of education in Rumberu Village and to find out the factors of children’s desire to attend education in Rumberu Village. This research was conducted in Rumberu Village, Inamosol District West Seram Regency. Primary data collection was carried out through interviews with a number of informants who were considered to be to be directly infolved. Data collection techniques used are observation, interviews, and documentation. Based on the results of the research, it was found that the understanding of the Rumberu people about education was very advanced, because the community was of the view that the presence of education was very importan in increasing quality human resources in order to develop the village to be even better in the future so that the village could compete with villages in other places. Besides that there are factors that become the child’s desire to attend education itself. This is what then becomes the special attention of all parties in the area, bot the goverment, the community, and also related stakeholders to further improve what children want in attending education in Rumberu Village.